Green Production of Indolylquinones, Derivatives of Perezone, and Related Molecules, Promising Antineoplastic Compounds - René Gerardo Escobedo-González; Héctor Pérez Martínez; Ma. Inés Nicolás-Vázquez; Joel Martínez; Gabriela Gómez; Juan Nava Serrano; Vladimir Carranza Téllez; C. L. Vargas-Requena; René Miranda Ruvalcaba (Journal of Chemistry)
A green approach to produce the indolyl derivatives from four natural quinones (perezone, isoperezone, menadione, and plumbagin) was performed; in this regard, a comparative study was accomplished among the typical mantle heating and three nonconventional activating modes of reaction (microwave, near-infrared, and high speed ball milling or tribochemical), under solventless conditions and using bentonitic clay as a catalyst. In addition, the tribochemical production of isoperezone from perezone is also commented on. It is also worth noting that the cytotoxicity of the synthesized indolylquinones in human breast cancer cell was tested by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, with the 3-indolylisoperezone being the most active. The structural attribution of the target molecules was performed by typical spectroscopic procedures; moreover, the experimental and computed 1H and 13C NMR chemical shifts data, with previous acquisition of the corresponding minimum energetic structures, were in good agreement.